From design to interpretation: Lessons from a public health campaign promoting physical activity. (September 2014) - Goodwin, Denise May; Peerbhoy, Denise; Murphy, Rebecca; Stratton, Gareth
Objective: Rising inactivity has led to an increase in health promotion campaigns aimed at encouraging healthy behaviour change. While this has become common place, often practices advised by social marketing to maximise effectiveness are overlooked. This study investigates the development and effectiveness of one particular physical activity public health campaign implemented in Liverpool, United Kingdom (UK). A formative evaluation feedback session was included to communicate findings back to key stakeholders to reflect on the experience and identify learning points for future campaigns. Design: Based on a pragmatic paradigm the study was conducted in three parts: (1) campaign designer interview; (2) public on-street survey; and (3) stakeholder formative evaluation feedback session. Setting: The context of this study was Liverpool, UK. Method: Deductive content analysis was guided by key themes of the campaign design, including the poster image, tagline, main text, and overall layout. Results: The design team had aimed for a 'tongue in cheek' image and message on which to base the campaign. However, the public survey suggests that the campaign largely failed to translate the proposed message and reach the intended Liverpool population. Formative evaluation feedback highlighted a lack of application of social marketing principles in campaign development, in particular audience targeting and pilot assessment. Conclusion: This study highlights the importance of the inclusion of social marketing principles in the development of health promotion campaigns in an attempt to aid audience understanding and adoption of the desired health behaviour.